(untitled) (Географический вестник=Geographical bulletin, 2017)
Проведены исследования динамики кучево-дождевой облачности, выявлены причины изменчивости движения конвективной облачности. Рассмотрены стадии развития градовых процессов, определены уровни образования града и температурный интервал. Разработан метод определения условий зарождения и роста града в облаках на основе численной модели формирования облачных частиц. DYNAMICS OF DEVELOPMENT HAILSTORM IN THE PERM Researches of dynamics of Сb overcast are conducted, the reasons of variability of movement of convective overcast are established. Development stages hailstorm processes are considered, educational levels of hailstones and a temperature interval are defined. The method of definition of conditions of origin and hailstones growth in clouds on the basis of numerical model of formation of cloudy particles is developed.